Harvard business essentials coaching and mentoring - Harvard Business School (Boston Harvard Business School Press, 2004)
Effective managers know that timely coaching can dramatically enhance their teams' performance. Coaching and Mentoring offers managers comprehensive advice on how to help employees grow professionally and achieve their goals. This volume covers the full spectrum of effective mentoring and the nuts and bolts of coaching. Managers learn how to master special mentoring challenges, improve listening skills, and provide ongoing support to their employees. The Harvard Business Essentials series is designed to provide comprehensive advice, personal coaching, background information, and guidance on the most relevant topics in business. Drawing on rich content from Harvard Business School Publishing and other sources, these concise guides are carefully crafted to provide a highly practical resource for readers with all levels of experience and are especially valuable for the new manager. To assure quality and accuracy, a specialized content adviser from a world-class business school closely reviews each volume. Whether you are a new manager seeking to expand your skills or a seasoned professional looking to broaden your knowledge base, these solution-oriented books put reliable answers at your fingertips.
Includes bibliographical references (p. 149-152)
Keywords: Mentoring in business. Employees --Coaching of